Предмет: Алгебра,
автор: nikolaysorokin4
Помогите, срочно
Решите уравнение:
1)(x+3)(x-3)-x(x+4)=0
2)3x(1+12x)-(6x-1)(6x+1)=2,5x
Ответы
Автор ответа:
0
1)x^2-9-x^2-4x=0
-4x=9
x=9/(-4)
x=-2,25
2)3x+36x^2-(36x^2-1)=2,5x
3x+36^2-36^2+1=2,5x
3x-2,5x=-1
0,5x=-1
x=-1/0,5
x=-2
-4x=9
x=9/(-4)
x=-2,25
2)3x+36x^2-(36x^2-1)=2,5x
3x+36^2-36^2+1=2,5x
3x-2,5x=-1
0,5x=-1
x=-1/0,5
x=-2
Автор ответа:
0
Спасибо
Похожие вопросы
Предмет: Математика,
автор: masho77705
Предмет: Алгебра,
автор: isostata54
Предмет: История,
автор: lisalizakov2008
Предмет: Геометрия,
автор: zayapoprygaya
Предмет: Алгебра,
автор: гордиенко1598753